2017
DOI: 10.1021/acs.jced.6b00848
|View full text |Cite
|
Sign up to set email alerts
|

Hydrate Dissociation Equilibrium Conditions for Carbon Dioxide + Tetrahydrofuran

Abstract: Hydrate equilibrium conditions (vapor + hydrate + liquid water + liquid tetrahydrofuran, THF) formed from carbon dioxide in aqueous solutions of THF is determined using a stepwise heating method under isochoric conditions in this work. THF is reported to form an SII hydrate. Hydrate phase equilibrium conditions are measured under the conditions of the THF mass concentration range of 0.0726−0.2503 and pressure range of 0.10−1.87 MPa. The experimental results present that the equilibrium pressures of the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 24 publications
(35 reference statements)
3
11
0
Order By: Relevance
“…THF is a water-miscible substance forming an SII hydrate structure without any guest gas below 4.4 °C at atmospheric pressure . Several researchers used THF as a thermodynamic promoter to reduce the equilibrium pressure of hydrate formation of guest gases like CO 2, , nitrogen, methane, , propane, and hydrogen . Recently, Veluswamy et al reported an enhancement in the kinetics of methane hydrate formation in the presence of THF; however, the authors did not achieve a similar result for CO 2 hydrate formation kinetics in their subsequent work .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…THF is a water-miscible substance forming an SII hydrate structure without any guest gas below 4.4 °C at atmospheric pressure . Several researchers used THF as a thermodynamic promoter to reduce the equilibrium pressure of hydrate formation of guest gases like CO 2, , nitrogen, methane, , propane, and hydrogen . Recently, Veluswamy et al reported an enhancement in the kinetics of methane hydrate formation in the presence of THF; however, the authors did not achieve a similar result for CO 2 hydrate formation kinetics in their subsequent work .…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the process of hydrate formation in hydrate-based technologies, especially CO 2 sequestration and hydrate-based desalination (HBD), the use of porous media, thermodynamic additives, , and/or kinetic additives as a promoter is well accepted. Thermodynamic promoters are the chemical additives that reduce the hydrate formation pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that it can bring a significant reduction of the phase equilibrium pressure for the CO 2 hydrate with the mass fraction of THF over 0.05. Moreover, Wang et al reported that THF has an inhibitory effect on the CO 2 hydrate when the mass fraction is above 0.1905. TBAB can also react with water to form a semiclathrate hydrate, which contains two crystal structures, that is, TBAB·26H 2 O (structure A) and TBAB·38H 2 O (structure B). , TBAB has a great influence on the phase equilibrium of a gas hydrate.…”
Section: Introductionmentioning
confidence: 99%
“…Promoters include kinetic promoters and thermodynamic promoters. Thermodynamic promoters usually improve the equilibrium conditions of hydrate formation by filling hydrate cages and increase the driving force of hydrate formation. Delahaye et al studied the effect of tetrahydrofuran (THF) with a mass concentration of 3.98–15.00 wt % on the equilibrium conditions of CO 2 hydrate.…”
Section: Introductionmentioning
confidence: 99%
“…Their studies showed that the reduction of the equilibrium pressure of CO 2 hydrate will increase with the increase of the mass fraction of THF. Wang et al also investigated the influence of THF on the equilibrium conditions of CO 2 hydrate and showed that, when the mass fraction of THF is higher than 19.05%, more THF inhibit the formation of CO 2 hydrate. Some semi-clathrate hydrate formers, for instance, tetra - n -butyl ammonium bromide (TBAB), tetra - n -butyl ammonium fluoride (TBAF), and tetra - n -butyl ammonium chloride (TBAC), also improve the phase equilibrium conditions of CO 2 hydrate. , …”
Section: Introductionmentioning
confidence: 99%